The Relationship Between the Physical Condition of Water (Taste, Smell, Color) and Complaints of Skin Diseases in Simalingkar B Village - Lauchan, Agil Maritho; Nanda, Meutia; Melisa, Melisa; Amrainum, Desri; Ritonga, Indah Rahayu; Az Zahra S., Alya (PROMOTOR, 2024)
The physical condition of unclean water can cause skin disorders this is because unclean water is polluted by physical particles, pathogenic microorganisms, and harmful chemicals can cause various skin diseases. the study aims to determine the relationship between the physical condition of water (color, smell, taste) with complaints of skin disease disorders in Simalingkar B Village. In this study using quantitative methods with a cross sectional design. The population in this study was people who used well water, obtained 2,531 families using well water with sampling using the purposive sample formula so that 93 families were sampled for this study. The results of the study showed a relationship between the physical condition of water (taste, odor, color) with complaints of skin disorders in Simalingkar B Village with the results of statistical tests obtained p value 0.029 or <0.05, meaning that at 5% alpha indicates a relationship between the quality of clean water with the incidence of scabies in Simalingkar B Village. Obtained OR value = 2.815 which indicates that respondents who have a water source with physical quality of clean water that does not meet the requirements have a risk of 2.815 times to suffer from skin disorders compared to respondents who have a water source with physical quality of clean water that meets the requirements. The government and community can work together to establish clean water reservoirs to prevent skin diseases in Simalingkar B Kelurahan.